LEGAL CONSEQUENCES OF NOT DELETING A REGISTERED FIDUCIARY SECURITY IN THE ONLINE SYSTEM IN BALI PROVINCE - Kadek De Adnyana; Ketut Sukawati P Perbawa; Lis Julianti; Putu Lantika Oka Permadhi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research analyzes the legal consequences of not removing Fiduciary guarantees registered in the online system in the province of Bali. The implementation of the elimination of Fiduciary guarantees registered in the online system is the obligation of Fiduciary recipients as creditors, this provision is regulated in Article 16 paragraph (2) of Government Regulation Number 21 of 2015 concerning Procedures for Registration of Fiduciary Guarantees And the cost of making a Fiduciary Guarantee Deed. However, in practice there are still fiduciary recipients, namely creditors who do not fulfill their obligations to abolish the fiduciary guarantee after the fiduciary giver, namely the debtor, has fulfilled all his achievements. There is no sanction that regulates related if the Fiduciary recipient does not eliminate the Fiduciary guarantee which results in this obligation being disobeyed. The study of this research is related to the implementation of the elimination of Fiduciary guarantees registered in the online system and the legal consequences of the negligence of the Fiduciary recipients for not notifying the Fiduciary guarantee deletion to the Minister registered in the online system. The method used is an empirical legal research method. The analytical knife of legal issues in this thesis is the theory of legal effectiveness, the theory of legal certainty and the theory of legal protection. The results that can be concluded in this study are if the Fiduciary recipient, his proxy or his representative does not notify the removal of the Fiduciary guarantee, then the Fiduciary guarantee concerned cannot be re-registered.